IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING PADA PEMILIHAN SEPATU SPORT BERDASARKAN BAHAN BAKU - Tonni Limbong; Andy Paul Harianja (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
The increasingly advanced zone of sport shoes is one of the needs needed to increase comfort in sports activities, sport shoes can also increase one's confidence. Decision Support Systems or DSS is a technique of mathematically based information systems including knowledge-based systems or knowledge management that are used to support making decisions in an organization or company. Simple Additive Weighting method is a method in decision support based on the concept that a good alternative not only has the basic criteria but also the best solution but also has a number of recommendations for shoe selection based on the raw material that is expected. Keywords: Sport Shoes, Decision Support System, Simple Additive Weighting..